A Prospective Study of Asymptomatic Intracranial Atherosclerotic Stenosis in Neurologically Normal Volunteers in a Japanese Cohort - Matsui, Ryukichi; Nakagawa, Tomonori; Takayoshi, Hiroyuki; Onoda, Keiichi; Oguro, Hiroaki; Nagai, Atsushi; Yamaguchi, Shuhei (Frontiers in Neurology, 2016)
Atherosclerotic stenosis of major intracranial arteries is a leading cause of ischemic stroke in Asia. However, the long-term prognosis of asymptomatic intracranial atherosclerotic stenosis (ICAS) in healthy volunteers has not been fully examined. Here we conducted a longitudinal study to examine the prognosis of healthy volunteers with asymptomatic ICAS and to determine the risk factors for ICAS, including asymptomatic brain parenchymal lesions. We studied 2,807 healthy Japanese volunteers with no history of stroke (mean age, 62.0 years). They were followed for a mean interval of 64.5 months. The degree of ICAS and the presence of asymptomatic brain lesions were assessed by using magnetic resonance imaging. Asymptomatic ICAS was detected in 166 volunteers (5.9%) at the initial examination. Moderate and mild stenoses were observed in 1.5% and 4.4% of patients, respectively. Significant risk factors for ICAS were older age and a history of hypertension, and/or dyslipidemia. During follow-up, ischemic stroke developed in 32 volunteers. Seven strokes occurred in the ICAS group, whose stroke incidence rate was higher than that in the non-ICAS group (0.78% vs. 0.18% per year). According to a Cox regression analysis, asymptomatic ICAS was an independent risk factor for future ischemic stroke after adjustment for age. Furthermore, after asymptomatic brain lesions were taken into account, ICAS was still a significant risk factor for stroke onset. In conclusion, even mild to moderate asymptomatic ICAS was a significant risk factor for future stroke, independent of asymptomatic brain lesions, in a healthy Japanese population. Mild to moderate ICAS might be a therapeutic target for stroke prevention.